THE LANGUAGE OF PARENTING: REVEALING THE USAGE OF CONTROL ACTS IN THE PURSUIT OF HAPPYNESS - Kurniawan, Kurniawan (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2023)
In paternal parenting, compared to the mother, the father tends to use controlling language that provokes conversation, such as WH questions and requests for clarification. Controlling language (control acts) is an attempt to generate a change in the actions of others. Through a pragmatic approach, this qualitative study explores the strategy, pattern, and politeness of controlling language through a paternal parenting perspective. The present study used the theory of controlling language by Ervin-Tripp et al. (1990), direct or indirect speech acts by Searle (1971), and Brown and Levinson's theory of politeness (1987). The data in this study are the directive utterances in the film The Pursuit of Happyness. These data were collected through content analysis through listening and note-taking technique and analyzed using Spradley (2016). The study found 117 directive speech act data. From the data, order/command of control acts was the dominant act with 56 data. Besides, the most politeness strategy used was positive politeness. The study's finding suggests that all fathers pay more attention to parenting their children because they play a vital role in children's cognitive development. Moreover, in Indonesian society, patriarchy prevails, where fathers act as breadwinners and mothers nurture and educate children at home.